Aflatoxin B1 exposure and liver cirrhosis in Guatemala: a case–control study. Issue 1 (7th July 2020) - Alvarez, Christian S; Hernández, Elisa; Escobar, Kira; Villagrán, Carmen I; Kroker-Lobos, María F; Rivera-Andrade, Alvaro; Smith, Joshua W; Egner, Patricia A; Lazo, Mariana; Freedman, Neal D; Guallar, Eliseo; Dean, Michael; et al.
Abstract : Objective: In Guatemala, cirrhosis is among the 10 leading causes of death, and mortality rates have increased lately. The reasons for this heavy burden of disease are not clear as the prevalence of prominent risk factors, such as hepatitis B virus, hepatitis C virus and heavy alcohol consumption, appears to be low. Aflatoxin B1 (AFB1 ) exposure, however, appears to be high, and thus could be associated with the high burden of cirrhosis. Whether AFB1 increases the risk of cirrhosis in the absence of viral infection, however, is not clear. Design: Cirrhosis cases (n=100) from two major referral hospitals in Guatemala City were compared with controls (n=200) from a cross-sectional study. Logistic regression was used to estimate the ORs and 95% CIs of cirrhosis and quintiles of AFB1 in crude and adjusted models. A sex-stratified analysis was also conducted. Results: The median AFB1 level was significantly higher among the cases (11.4 pg/mg) than controls (5.11 pg/mg). In logistic regression analyses, higher levels of AFB1 was associated with cirrhosis (quintile 5 vs quintile 1, OR: 11.55; 95% CI 4.05 to 32.89). No attenuation was observed with adjustment by sex, ethnicity, hepatitis B virus status, and heavy alcohol consumption. A significantly increasing trend in association was observed in both models (p trend <0.01). Additionally, the cirrhosis–AFB1 association was more prominent among men. Conclusions: The current study found a significant positive association between AFB1 exposure and cirrhosis. Mitigation of AFB1 exposure and a better understanding of additional risk factors may be important to reduce the burden of cirrhosis in Guatemala.